Blood Requests and Utilization in Elective Surgical Patients in a Nigerian Teaching Hospital. (28th October 2020) - Olatinwo, A T; Bolarinwa, A; Adeyemo, T
Abstract: Introduction/Objective: Although requesting for blood is a very common practice for patients for surgical interventions, the average requirement for a particular procedure is usually based on subjective anticipation of blood loss rather than on evidence based estimates. Over-ordering of blood components results in wasting of technical time, reagents and imposes extra cost on patients. The objective of this study is to assess blood ordering and utilization in a Nigerian Tertiary Hospital. Methods: A review of one year data collected from the records of all discharged surgical patients and blood bank registers was done. Blood utilization was calculated using crossmatch to transfusion ratio (C/T), transfusion probability (%T), and transfusion index (TI). Results: A crossmatch request for 1, 228 units for 569 patients was made. Requests was higher for gynaecological cases (24.8 %) followed by orthopaedic procedures and least for cardiothoracic and urological surgeries (1.4 % each). Out of the crossmatched units, 880 units was transfused for 373 patients. The overall of C/T, %T, and TI were 1.4, 65.6%, and 1.55 respectively. The highest C/T was observed in elective caesarean sections (2.25) and neurosurgeries (2.2) while the lowest C/T was observed in oral maxillofacial surgeries (1.09) Conclusion: Unnecessary crossmatching with minimal transfusion practice was observed in many elective surgical cases. Blood request pattern for elective surgeries needs to be revised and unnecessary requests minimized. There is a need for a Hospital blood transfusion committee which should come up with blood request policies and transfusion guidelines for elective surgical procedures and also conduct regular blood transfusion service audits.